Synthesis of New Pyrazoline - Phenoxathiin Derivatives (Baghdad Science Journal, 2013)
Phenoxathiin was prepared by the reaction of diphenyl ether with sulfur in the presence of anhydrous aluminum chloride. This work comprised the synthesis of new phenoxathiin derivatives containing heterocyclic moieties. These heterocyclic compounds were synthesized in three groups. The first group was made up of 2-(oxoalken-1-yl) phenoxathiin derivatives (3a-3j) obtained from the reaction of 2-acetylphenoxathiin with different aromatic aldehyde in the presence of sodium hydroxide. The other two groups involved compounds produced from the reaction of (3a-3j) with hydrazine hydrate in acetic acid to get 2-(1-acetyl pyrazolin-3-yl) phenoxathiin derivatives (4a-4j), and phenyl hydrazine in the presence of piperidine to afford 2-(1-phenyl pyrazolin-3-yl) phenoxathiin derivatives (5a-5j). All these compounds of two groups above were substituted in position (5) in pyrazoline ring with different aryl groups according to aromatic aldehyde used in the preparation of the first group series compounds.